The Effect of Stock Selection Ability, Market-Timing Ability, and Fund Cash Flow on the Performance of Sharia Equity Mutual Funds (Study During the Covid-19 Pandemic, 2020-2021): Pengaruh Stock Selection Ability, Market Timing Ability, dan Fund Cash Flow Terhadap Kinerja Reksa Dana Saham Syariah (Studi Pada Masa Pandemi Covid-19 Tahun 2020-2021) - Rakhmad Pambudi Budi; Mahendra Galih Prasaja; Agus Saur Utomo (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2023)
Abstract: The Coronavirus pandemic has had an extraordinary impact on the economies of countries in the world, including Indonesia. This economic condition was reflected in the collapse of the stock market index in Indonesia. Mutual funds are an investment alternative that has convenience for investors who want to invest but need more investment skills and time. Islamic stock mutual funds are one of the choices in investing because Sharia values guide their management. The performance of Islamic equity mutual funds during the Covid-19 pandemic has declined; the number of Islamic equity mutual funds looks stagnant, while the NAV value has fallen. This study aimed to test the effect of stock selection ability, market-timing ability, and fund cash flow on the performance of Islamic equity mutual funds during the Covid-19 pandemic. The population in this study is all Islamic equity mutual funds traded during the 2020-2021 period. The sampling technique in this study used purposive sampling. The samples obtained were 39 Sharia equity mutual funds that reported monthly NAV on the OJK website. The data were tested using regression with the help of Eviews software version 12. The results of this study indicate that stock selection ability, market-timing ability, and fund cash flow partially have a positive and significant effect on the performance of Islamic equity mutual funds. Abstrak: Pandemi Coronavirus berdampak luar biasa bagi perekonomian negara-negara di dunia termasuk Indonesia. Kondisi ekonomi tersebut tercermin pada runtuhnya IHSG pasar modal di Indonesia. Reksa dana merupakan salah satu alternatif investasi yang memiliki kemudahan bagi para investor yang ingin berinvestasi tetapi memilliki keterbatasan keahlian investasi dan waktu. Reksa dana saham syariah dijadikan salah satu pilihan dalam berinvestasi dikarenakan pengelolaannya yang berpedoman pada nilai-nilai syariah. Kinerja reksa dana saham syariah pada masa pandemi covid-19 terlihat menurun, jumlah reksa dana saham syariah terlihat stagnan sedangkan nilai NABnya turun. Tujuan penelitian ini untuk menguji menguji pengaruh stock selection ability, market timing ability, dan fund cash flow terhadap kinerja reksa dana saham syariah pada masa pandemi covid-19. Populasi dalam penelitian ini adalah seluruh reksa dana saham syariah yang diperdagangkan selama periode 2020-2021. Teknik pengambilan sampel pada penelitian ini menggunakan purposive sampling. Sampel yang diperoleh sebanyak 39 reksa dana saham syariah yang melaporakan NAB bulanan di website OJK. Data diuji dengan menggunakan regresi dengan bantuan software Eviews versi 12. Hasil penelitian ini menunjukkan bahwa stock selection ability, market timing ability, dan fund cash flow secara parsial berpengaruh positif dan signifikan terhadap terhadap kinerja reksa dana saham syariah.